Proposta de reatores eletrônicos para iluminação com alto desempenho - Demian Junior, Aziz Elias (2008)
This work presents the development and implementation of an electronic ballast prototype to supply high frequency HID lamps and another one to LED lamps. The use of these devices provides many benefits, such as high-performance, reduced weight and size and a possibility to provide special functions. All the intermediate states will be presented, which explains the theoretical study of the HID and LED lamps, as well the converters used on their drives. In this project, a Microchip microcontroller was used to control the ballast of HID and LED lamps. The reason is its high flexibility. It is possible to change drive methods. The digital controllers have the additional intellectual/industrial protection when desired. The microcontroller used was PIC 16F873A from Microchip, which is an inexpensive component, has many resources that enhance the control of converters. These resources may include five A/D converters, two PWM channels and serial communication.